Impact of vaccination on electrocardiograms of hospitalized patients for Covid-19 - Marco Mele; Lucia Tricarico; Antonio Centola; Federica Mango; Andrea Favia; Francesca Croella; Valeria Le Rose; Andrea Cuculo; Irene Bottalico; Maria Cristina Poliseno; Sergio Lo Caputo; Teresa Santantonio; et al. (Vaccine: X, 2023)
Introduction: We sought to assess the impact of SarsCov-2 vaccination on admission12-lead electrocardiogram of hospitalized patients. Methods: We retrospectively analyzed and compared admission 12-lead electrocardiograms of all patients hospitalized in dedicated Internal Medicine Unit for Covid-19 both in pre-vaccination period (PV) and after vaccination (V). Results: 667 consecutive Covid-19 in-patients were enrolled in the study: PV hospitalized patients were older (68vs57 years, p < 0.01), had higher rates of atrial fibrillation/flutter (13%vs2.5%, p < 0.01), any arrhythmia (26%vs8%, p < 0.01), and ST-T abnormalities (22%vs7.4%, p < 0.01). Mortality rates in hospitalized Covid-19 patients were higher before vaccination period (20%vs4%, p < 0.01). Minimal vaccination coverage of population (V period) was inversely and independently associated with in-hospital mortality (odds ratio 0.09, 95%CI 0.01–0.68, p < 0.05). Conclusions: SarsCov-2 vaccination campaign and even partial coverage of local population was associated with less frequent abnormalities at admission ECG in hospitalized non-critically hill Covid-19 patients and lower mortality.